JOHN B. SIMON, STRANGERS IN A STRANGER LAND - BERNHEIM, MARK (Society Register, 2021)
This is a book review of "STRANGERS IN A STRANGER LAND: How One Country's Jews Fought an Unwinnable War Alongside Nazi Troops…and Survived"; by John B. Simon; Rowman and Littlefield; 2019 (originally published in Finnish as Mahdoton sota, "The Impossible War," by Siltala Publishing, 2017). The review was written for the Jewish Book Council by a Professor Emeritus of English and contains both historical and pedagogical reflections on the educational messages emmerging from the book. This is important not only for memory studies and for identity politics but also when looking deep into the complex issues of socialization and education after the WWII. The book contains a story of the contradictory role of Finland's Jewish community in the wars against the Soviet Union and Germany.